Heterosis studies for grain yield and yield attributes in rice (Oryza sativa. L) hybrids - T. Ramakrishna1*, L. Krishna2, Y. Chandra mohan2, V. Gouri Shankar3 and D. Saida Naik4 (Electronic Journal of Plant Breeding, 2023)
In the current study, 20 elite rice genotypes were crossed with four CMS lines- CMS 23A, CMS 59A, CMS 64A and JMS 13A in a line x tester mating design and assessed alongside standard controls (JKRH 3333 and MTU 1001) to determine the best heterotic combinations in terms of grain yield and yield component characters at the Rice Research Centre, Rajendranagar. Eight restorer lines were found in Kharif 2018–19 based on pollen and spikelet fertility (MTU 1153, RNR 26015, RNR 28355, JGL 25960, MTU 1010, IET 27253, RNR 26085 and JAYA). The resulting 32 hybrids of 8 restorer lines and their corresponding CMS lines are studied for combing ability and heterosis. The degree of heterosis varied between traits. Three of the 32 hybrids under study had considerable standard heterosis for grain yield viz., JMS 13A x MTU 1153, CMS 59A x RNR 26015 and CMS 64A x MTU 1153, which outperformed the best checks JKRH 3333 and MTU 1001. The best experimental hybrid, JMS 13A x MTU 1153, yielded the most grain yield per plant, 62.89g (Table 1). Further testing of these three experimental hybrids will take place in areas conducive to extensive commercialization.